ChemInform Abstract: Alcohols as Alkylating Agents in Heteroarene C—H Functionalization. Issue 4 (January 2016) - Jin, Jian; MacMillan, David W. C.
Abstract: A mild and simple alkylation reaction utilizing a combination of photoredox and thiol hydrogen atom transfer organocatalysis for the formation of heteroaryl C—C bonds using alcohols as latent nucleophiles is developed.